2015
DOI: 10.3386/w21812
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Its (Dis-)Content: Trade Shocks and Voting Behavior

Abstract: We identify the causal effect of trade-integration with China and Eastern Europe on voting in Germany from 1987 to 2009. Looking at the entire political spectrum, we find that only extreme-right parties respond significantly to trade integration. Their vote share increases with import competition and decreases with export access opportunities. We unpack mechanisms using reduced form evidence and a causal mediation analysis. Two-thirds of the total effect of trade integration on voting appears to be driven by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 50 publications
4
90
1
1
Order By: Relevance
“…37 Autor et al (2016) and Dippel et al (2015) provide evidence consistent with the idea that trade-induced changes in inequality can alter the political equilibrium, even in "full democracies". In particular, these works show that import competition, and the associated increase in inequality, lead to political polarization and the rise of more "extremist" parties in, respectively, the US and Germany.…”
supporting
confidence: 60%
“…37 Autor et al (2016) and Dippel et al (2015) provide evidence consistent with the idea that trade-induced changes in inequality can alter the political equilibrium, even in "full democracies". In particular, these works show that import competition, and the associated increase in inequality, lead to political polarization and the rise of more "extremist" parties in, respectively, the US and Germany.…”
supporting
confidence: 60%
“…The regional control variables include factors that may affect both political attitudes and the income distribution, such as net migration rates, economic growth, and the level and growth of manufacturing jobs. I control for manufacturing jobs as there is empirical evidence that increasing regional exposure to trade with lower income countries during this period led to the destruction of manufacturing jobs and stronger support for extreme political parties (see Dippel et al., ; Malgouyres, ). The estimates of β are positive and very similar to the baseline results in Table , implying that inequality had an impact on political polarization beyond any contemporaneous changes on immigration flows, economic growth, and manufacturing jobs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent empirical evidence has shown that trade shocks, which have reduced demand for local manufacturing (and have therefore led to job losses), have contributed to the increasing polarization observed in the United States (Autor, Dorn, Hanson, & Majlesi, ). Similarly, exposure to trade with low‐income countries in France and Germany has been linked to the rise of extreme right political parties (Dippel, Gold, & Heblich, ; Malgouyres, ). Immigration has also been associated with political polarization in Austria, where higher immigrant inflows have increased the share of votes received by the far right‐wing political party, with residents voicing concerns about the effects of immigrants on the labor market along with “compositional amenities” (Halla, Wagner, & Zweimüller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar polarizing trends were evident in Western Europe where the negative employment effects of manufacturing imports from China were linked to rising support for more right‐wing and protectionist political parties (Colantone & Stanig, ). In Germany, however, political polarization was delayed by strong growth in manufacturing exports, a more balanced regional distribution of industry, and active labour‐market policies to assist workers displaced by trade shocks (Dippel et al, :36). That was not the case in Britain.…”
Section: Uneven and Combined Development: The Conjuncture Of 2016mentioning
confidence: 99%